Production Management of White Snapper Lates calcarifer Reared in Floating Net Cage - Iskandar, Andri; Situmeang, Tulus Romora; Indriastuti, Cecilia Eny (Journal of Vocational in Aquaculture (JAVA), 2025)
The cultivation of white snapper Lates calcarifer, also known as sea bass or barramundi, is gaining popularity in commercial aquaculture because of its fast growth and ease of maintenance. This study explores various aspects of white snapper farming in floating net cages (KJA) in Indonesia, a region where the species thrives in coastal waters and estuaries. Government support for marine aquaculture, particularly for white snapper, has contributed to increased production to meet the rising domestic and international demand. This research focuses on site preparation, seed stocking, feeding, water quality management, and disease prevention. The results indicated that maintaining optimal water conditions, careful feeding strategies with a mix of pellet and trash fish, and regular health monitoring are essential for successful cultivation. A key challenge is the prevention of benedeniasis, a parasitic infection managed through hydrogen peroxide treatments. The findings emphasize the importance of efficient farming practices to enhance productivity and profitability while ensuring environmental sustainability. The information provided serves as a reference for aquaculture business operators and contributes to the advancement of white snapper farming in Indonesia.